Functional identification of AtAVT3, a family of vacuolar amino acid transporters, in Arabidopsis. Issue 1 (19th December 2016) - Fujiki, Yuki; Teshima, Hiromitsu; Kashiwao, Shinji; Kawano‐Kawada, Miyuki; Ohsumi, Yoshinori; Kakinuma, Yoshimi; Sekito, Takayuki
Abstract : Amino acids stored in the vacuoles are exported to the cytosol mainly for protein synthesis; however, the molecular identity of vacuolar amino acid exporters remains obscure in plants. Here, we demonstrate that the heterologous expression of AtAVT3 genes, Arabidopsis homologs of AVT3 and AVT4 encoding vacuolar amino acid exporters in yeast, reduces vacuolar amino acid levels in the avt3 ∆ avt4 ∆ yeast cells. In vitro experiments revealed that 14 C‐labeled Ala and Pro are exported from vacuolar membrane vesicles by AtAvt3A in an ATP‐dependent manner. In Arabidopsis, AtAvt3A fused with green fluorescent protein localizes to the vacuolar membrane. We propose that AtAVT3 family represents the long sought‐for vacuolar amino acid exporters in plants.